Penggunaan Web Quizizz pada Pelajaran Fisika Materi Energi Kinetik dan Energi Potensial di Kelas X.7 SMA Negeri 1 Pekanbaru - Afdal Dinilhaq; Suryani Dasmilena; Pratama Benny Herlandy (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This research is motivated by the importance of utilizing technology-based learning media to enhance the effectiveness of the learning process, particularly in Physics subjects that are often perceived as difficult by students. The purpose of this study is to describe the use of Quizizz as a learning media in Physics lessons on Kinetic Energy and Potential Energy material in class X.7 of SMA Negeri 1 Pekanbaru. This study employed a descriptive qualitative method with data collection techniques through observations and documentation of students' learning outcomes. The results showed that the use of Quizizz successfully created an enjoyable learning atmosphere, increased students' motivation, and encouraged active participation. The evaluation scores through Quizizz indicated an improvement in students’ understanding of the material, with the highest score reaching 5000 points. The implication of this research suggests that implementing game-based learning media such as Quizizz can serve as an innovative alternative to improve student learning outcomes and reduce boredom in Physics learning.